Journal Economics, business & accountancy: THE DESIGN OF SPENCER GENERIC COMPETENCY AS A MODEL FOR BANKING SUPERVISORS POSITION SPECIFICATION IN SURABAYA - Irawan (PPPM Perbanas, 2011)
Banking industries have some targets in which the supervision of banks is required. In orderthat the banks can strengthen the national banking industry fundamental, Bank Indonesia(BI) implements Indonesia Banking Architecture (IBA). The second target of the ABI is tocreate a system of independent and effective bank regulation and supervision based on internationalstandards. This study attempts to uncover some issues such as (1) How to designgeneric competencies of Spencer as a model specification for the Supervision of Banking officesin Surabaya; (2) How technical competence and perceived behavioral competencies ascompetencies are required for Banking Supervision. This study uses 50 bank branch managersin Surabaya as respondents.